Clarithromycin resistance and point mutations in the 23S rRNA gene in Helicobacter pylori isolates from Malaysia - Ho, Sin-Loong; Tan, E.L.; Sam, C.K.; Goh, K.L. (2010)
OBJECTIVE: To determine the prevalence of primary clarithromycin resistance amongst Helicobacter pylori (H. pylori) strains in Malaysian patients with gastroduodenal diseases, by using restriction fragment length polymorphism (RFLP) in domain V of 23S rRNA. METHODS: Gastric biopsies were obtained from H. pylori positive patients undergoing gastroscopy. DNA extraction was followed by PCR amplification using the primers Hp23-1 and Hp23-2 flanking a region of 425bp within the bacterial 23S rRNA peptidyltranferase (Hp23S fragment). Analysis of the 23S rRNA gene mutations is based on the generation of restriction sites for two restriction enzymes: BbsI and BsaI, which correspond to the base substitutions characteristic of clarithromycin resistance from A to G at positions 2142 and 2143, respectively. RESULTS: Gastric biopsy samples were obtained from 107 patients. A fragment of size 425bp corresponding to that expected from amplification of domain V of 23S rRNA was PCR-amplified from only 105 samples. The amplicon was subsequently subjected to restriction by BbsI and BsaI. Only 1 sample (0.95%) had the BbsI mutation (base substitution at A2142G) and 2 samples (1.90%) the BsaI mutation (base substitution at A2143G). Thus 3 of 105 (2.9%) samples harbored clarithromycin resistant strains. CONCLUSION: In our experience, PCR-RFLP is a rapid and precise method to detect the resistance of H. pylori to clarithromycin. Using this method, a low prevalence of clarithromycin resistance was detected in our local Malaysian strains. This augurs well for the continued use of clarithromycin as a first line drug in the treatment and eradication of H. pylori infection.